Definitions of the calorific value of fules - British Standards Institution (London BSI, 1961)
Fuels, Calorific value, Definitions, Gaseous fuels, Liquid fuels, Solid fuels, Formulae (mathematics), Heat measurement
Superseded, Withdrawn
Cross References BS 350:Part 1, BS 1016:Part 5, BS 1016:Part 16
Replaced By BS 7420:1991
Keywords: Calorific value -- Standards